KECEMASAN REMAJA TUNANETRA DITINJAU DARI KONSEP DIRI DAN PERSEPSINYA TERHADAP REMAJA AWAS - Tin Suharmini (LPPM UNY, 2000)
Abstract This research was aimed to investigate correlation between: (1) self-concept and social anxiety, (2) perception toward normal teenagers and social anxiety (3)self-concept and perception toward normal teenagers both simultaneously to social anxiety. In addition, it was also aimed to reveal social anxiety differences between totally blind and low vision teenagers, male and female blind teenagers, those living at dormitory and outside dormitory, as well as those with in born blindness and those with school age blindness. Subjects in this research were108 blind teenagers attending at SLB/A in Central Java and Yogyakarta Special Territory Provinces during the academic year of 1995/1996. Data were collected by means of (1)self-report for studying blind teenager social anxiety, (2)questionnaires to reveal self-concept and perception toward normal teenagers. Data were the analyzed by regression analysis and variance analysis technique. The results of this research were: There was a negative correlation between self-concept and social anxiety in blind teenager (rxly=-0.6945; p0.01). (2) There was a negative correlation of perception toward normal teenagers to social anxiety (rxly=0.2276;p0.01). (3)There was a correlation between both of self-concept and perception toward normal teenagers to social anxiety in blind teenagers (ry12=0.713;p0.01) (4) There was no social anxiety difference among totally blind and low vision teenagers (F=0.165;p0.05) (5)There was no social difference between male and female blind teenagers (F=0.029;p0.05). (6) There was no social anxiety difference between blind teenagers living at dormitory and outside dormitory (0.002;p0.05). (7)There was no social anxiety difference between blind teenagers within born blindness and those with school age blindness (F=0.149;p0.05). (8) There was social anxiety differences between low vision male teenagers living outside dormitory and low vision female teenager living outside dormitory (t=2.10; p0.05). Low vision male teenagers group living outside dormitory had higher averaged scores than female low vision teenagers group living outside dormitory. These finding, it was concluded that social anxiety of blind teenagers was influenced by self-concept and perception toward normal teenagers. Self-concept exerted a greater influence on social anxiety than perception toward normal teenagers.